Testing the EKC Hypothesis Using Ecological Footprint by Considering Biocapacity and Human Capital in Türkiye: A Dynamic Analysis - Karahan-Dursun, Pınar (Panoeconomicus, 2024)
The study aims to investigate the validity of the environmental Kuznets curve (EKC) hypothesis, which asserts the inverted U-shaped relationship between economic growth and environmental pollution. The study uses ecological footprint (EF) as a measure of environmental degradation over the 1970–2017 period in Türkiye. Unlike the current literature for Türkiye, this study involves biocapacity and human capital in the growth–environment nexus and utilizes dynamic analysis. In this context, the Bound test, autoregressive distributed lag (ARDL) model, and Kalman filter approach are applied. The result of the Bound test confirms the cointegration relationship between the variables. The findings of the ARDL model indicate that the EKC hypothesis prevails, and biocapacity affects EF positively, whereas human capital mitigates environmental degradation by decreasing EF. The results of the dynamic analysis using the Kalman filter technique also validate the EKC hypothesis and show that the dynamic effect of economic growth on EF is significantly positive and stable for the analyzed period. JEL: Q5, C32